Produção extracelular de enzimas hidrolíticas por leveduras de solos roraimenses - Alencar, Andreia da Silva (2012)
In recent years the market for enzymes has grown a lot due to their use in specific reactions important for several industrial sectors. The micro-organisms, in particular, the yeasts are able to produce a wide variety of enzymes, and so, become ever more interesting for studies the use of your compounds. This work aimed to assess the capacity of production of hydrolytic enzymes by yeasts isolated from soils of the Viruá National Park and the Campus of Cauamé, in Roraima. The isolation process allowed to quantify 6,4x106 UFC/g, grouped into 11 morphtypes, and identified within four genuses: Candida, Cryptococcus, Rhodotorula and Yarrowia. Were identified Cryptococcus podzolicus, Candida pseudointermedia and Rhodotorula mucilaginosa; five isolates have been identified as new species, being four Yarrowia sp and one Candida sp, which are undergoing description. The isolates tested did not produce amylase and cellulase by tests used. Qualitative lipase production was observed in 36 % of the isolates, represented by Yarrowia spp. (VR546, VR547, VR571 e VR572). The protease was produced about 90% of the isolates: Cryptococcus podzolicus (VR520, VR535 and VR558), Candida sp. (VR533), Candida pseudointermedia (VR544 and VR545) and Yarrowia sp. (VR546, VR547, VR571 and VR572).Three isolates of Cryptococcus podzolicus (VR520, VR535 and VR558) produced xilanase e pectinase. The multienzymatic potential was observed in 63 % of the isolates, represented by Cryptococcus podzolicus (VR520, VR535 and VR558) and Yarrowia SP. (VR546, VR 547, VR571 and VR572). The results of this study confirm the importance of protected areas as sources of new species, including with special interest for biotechnology.